Algorithmic Synergy and Architectural Form Generation Mechanisms (Journal of Engineering, 2020)
Today, the architecture field is witnessing a noticeable evolution regarding the used tools that the designer should invest in a peculiar way that is made available in architecture through the concept of synergy generally and algorithmic synergy specifically. The synergy is meant to study and analyze the cooperative behavior of complex systems and self-organizing systems that leads to different outputs referred to by the synergy as the (whole), which is bigger than the sum of parts and in architecture, it's translated as the architectural form. This point resulted in a need of a specific study regarding the concept of synergy that focuses on the cooperative, synergistic relations within the trilogy of (form, structure, and material) and clarifies the role of technological evolution of design tools through algorithmic synergy in formulating that relation, thus resulted in the research's problem which came in the following statement (The lack of clear knowledge of the algorithmic synergy and its mechanisms in generating and discovering the architectural form digitally) and to solve this problem and Achieving the research goal which is represented in (Clarifying the knowledge regarding the role of algorithmic synergy and its mechanisms in generating and discovering the architectural form digitally), the research clarifies the concept of "Synergy" in general and "Algorithmic Synergy" precisely in order to get the epitome of vocabulary on the theoretical part and moving on to the practical application on elected projects samples  moving on to the conclusions and recommendations that shows having the architecture a self-organizing synergy system connects the designer and the developed digital tool that is provided by algorithmic synergy, plays a vital role in reaching the digitally synergized whole that represented by the architectural form.